PENGOLAHAN AIR TANAH DI WILAYAH BANGIL-PASURUAN MENJADI AIR MINUM DENGAN PROSES KLORINASI - Atiqotuzzummah, Atiqotuzzummah; Rahman, Nanik Astuti (Teknik Kimia ITN Malang, 2024)
Bangil area is a coastal area surrounded by industry. Groundwater ini Bangil Sub-district have poor quality impacted by surrounding conditions. One of the parameters of poor groundwater quality is the total plate count (TPC) value which reaches 151 x 10 colonies/ml with a standart of 1.0 x 102 colonies/ml. TPC value represents the number of microorganism colonies in the water. To reduce TPC value, its necessary to disinfect the microorganism in the water. One method that can be used is the chlorination process. The chlorination process by adding kaporit with kaporit variables 3 ppm, 4 ppm, and 5 ppm with reaction time 10 minutes, 20 minutes, 30 minutes, 40 minutes, and 50 minutes. Output from chlorination prcess will be analyzed for pH, TDS, TSS, turbidity, TPC, and residual Cl-. From the research, the TPC value decreased significantly and the best variable was obtained at a chlorine concentration of 5 ppm, with a reaction time of 50 minutes.